Malaysian crude palm oil market volatility: a GARCH approach - Haron, Razali; Ayojimi, Salami Monsurat (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This study aims to examine the volatility of Malaysian Crude Palm Oil (CPO) market for it has important implication to both business communities and policy makers. This study adopted the GARCH (1,1) model and the result of the finding exhibited persistent volatility as well as volatility clustering in Malaysian CPO market. The persistent volatility implies that the percentage of market volatility is closer to unity. This reflects the frequency of occurrence of the CPO market volatility while volatility clustering provides useful information on the broadness of the shock. Adequate understanding of the degree of volatility of the market can instigate informed decision by policy makers which may perhaps mitigate persistency of uncertainty of returns. Business communities on the other hand will be consistently alert on the voice of the market and ready to make sound decision on the events of the market. At the same time, the importance of hedging in Malaysian CPO futures market is empirically confirmed. This study contributes to the understanding on commodity market volatility by quantifying the half-life of decay of the shock in the market.